Remplissage Using Percutaneous Needle Navigation With Knotless Anchors in a Suture Staple Configuration - Carl Edge, M.D.; Carter Berry, B.S.; James Satalich, M.D.; J. Brett Goodloe, M.D. (Arthroscopy Techniques)
Remplissage is a procedure that decreases the rate of recurrent instability after arthroscopic stabilization in patients with an engaging Hill-Sachs lesion. This technique involves capsulotenodesis of the infraspinatus tendon and posterior capsule into the Hill-Sachs lesion using 2 knotless anchors with suture passage through the infraspinatus tendon guided by a percutaneous needle. Previously described techniques use knots or anchor placement through the infraspinatus, which can be challenging to control and irreversible if tendon penetration occurs in an undesirable location. Benefits of this technique include less manipulation within the subacromial space, precision with suture passage through the infraspinatus tendon and capsule to maximize spread, and decreased morbidity for the cuff tissue.